Development of a coir fibre extracting machine (2020)
The traditional methods of extracting fibres from the coconut husks are extremely tedious and time-consuming and not suitable for large scale production. The objective of the study was to develop an efficient and effective, low-cost, coir fibre extracting machine from locally available resources. The machine consists of the hopper, crushing, sieving and the power transmission units, which were manufactured using standard manufacturing techniques. From the design analysis, a 6hp electric motor was required to drive the 0.00938m3 hopper capacity machine to produce a torque of 11.8Nm at 3000rpm. The flat-belt required to transmit power from one pulley to the other was 1.5m long and had a groove angle of 170, and a torsional moment of 11.98Nm was acting on a shaft of diameter 30mm. Performance evaluation showed that the efficiency of the crushing unit and sieving units respectively ranged from 72 to 96% and 81.9 to 82.1% at 8.0% M.C. The average throughputs for the crushing and sieving units were; 14.5kg/hr and 13.9kg/hr respectively. The machine developed will serve as a time, labour and money saver in successful extraction of coir fibres for composite productions and other applications.